Teaching English Based on the Application of the Merdeka Curriculum at the MAN 1 Praya - Pauzan Pauzan (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This study seeks to explain how English instruction is implemented through the Merdeka Curriculum at MAN 1 Praya, Central Lombok. The participants included an English teacher, students, and the school principal. The research utilized both primary and secondary data gathered from three main sources: an English teacher who taught classes under the Merdeka Curriculum, students who experienced learning through this curriculum, and the principal. The researcher acted as the primary research instrument. The findings reveal several important points. First, to prepare for the implementation of the Merdeka Curriculum, English teachers participated in training sessions, workshops, and professional guidance programs. They also designed instructional materials aligned with the principles of the Merdeka Curriculum. Second, in classroom practice, teaching activities were organized into three stages: opening activities, core learning activities, and closing activities. Third, teachers conducted assessments based on the Merdeka Curriculum framework. However, challenges emerged, particularly in adapting their mindset due to the coexistence of two curricula, which led to differentiated instruction and additional administrative demands. As a solution, teachers attended workshops and engaged in collaborative knowledge-sharing to strengthen their understanding of the Merdeka Curriculum.